2005
DOI: 10.1111/j.1440-1789.2005.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic grain disease presenting with frontotemporal dementia: A neuropsychological and pathological study of an autopsied case with presenile onset

Abstract: A right-handed Japanese man with no consanguinity exhibited personality changes, speech disorder and abnormal behaviors, such as stereotypical, running-away, environment-dependent, and going-my-way behaviors, since the age of 49 years. At age 52 years, neuropsychological examination revealed frontal lobe dysfunctions, mild memory impairment, and transcortical sensory aphasia. MRI showed symmetrical severe atrophy of the anterior part of the temporal and frontal lobes. The clinical diagnosis was FTD. He died at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…However, it is still difficult to differentiate the individual pathologies, such as PSP from CBD, based solely on clinical presentation. The other entities in this group, MST, AGD and DNTC are rare when compared to PiD, PSP and CBD with only a handful of case reports or small case series of each of these pathologies being associated with FTD, PSPS or CBS [7, 26, 44, 45, 53, 71, 73, 93]. Therefore, no strong clinicopathological associations exist for MST, AGD and DNTC.…”
Section: The Frontotemporal Lobar Degenerationsmentioning
confidence: 99%
“…However, it is still difficult to differentiate the individual pathologies, such as PSP from CBD, based solely on clinical presentation. The other entities in this group, MST, AGD and DNTC are rare when compared to PiD, PSP and CBD with only a handful of case reports or small case series of each of these pathologies being associated with FTD, PSPS or CBS [7, 26, 44, 45, 53, 71, 73, 93]. Therefore, no strong clinicopathological associations exist for MST, AGD and DNTC.…”
Section: The Frontotemporal Lobar Degenerationsmentioning
confidence: 99%
“…However, in contrast to AD, there is only mild neuronal loss in limbic structures and, importantly, neocortical involvement in AgD is scarce [4,19] , a pattern which may account for the relative sparing of cognitive functions early in the course of AgD. Previous case studies of patients with AgD reported behavioral disturbances suggestive of frontotemporal dementia (such as inappropriate social conduct, egocentric, obsessive-compulsive, disinhibited behavior, dietary changes and apathy) [1,8] . Some of these reported cases [8] exhibited marked frontal and/or temporal lobe atrophy and widespread neocortical ArG, features which are not usually observed in AgD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case studies of patients with AgD reported behavioral disturbances suggestive of frontotemporal dementia (such as inappropriate social conduct, egocentric, obsessive-compulsive, disinhibited behavior, dietary changes and apathy) [1,8] . Some of these reported cases [8] exhibited marked frontal and/or temporal lobe atrophy and widespread neocortical ArG, features which are not usually observed in AgD. However, in the present study, patients displayed neither frontotemporal dementia-like symptoms nor neuropathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGD can occur alone or contextually to other neurodegenerative diseases, more often Alzheimer’s disease pathology (Fujino et al, 2005; Thal et al, 2005). The clinical presentation ranges from mild cognitive impairment to AD-like dementia and a slowly progressive bvFTD (Grinberg et al, 2013; Ishihara et al, 2005; Tsuchiya et al, 2001). Tau deposits in AGD lack acetylation, a post-translational modification step thought to be essential for the acquisition of pathogenic features by tau species in AD, hence the hypothesis of a potential protective role of AGD in AD that may explain the more benign clinical phenotype (slow disease course) often associated with this underlying neuropathology (Grinberg et al, 2013).…”
Section: Argyrophilic Grain Disease (Agd)mentioning
confidence: 99%